PENGARUH METODE BUKU CERITA BERGAMBAR TERHADAP KEMAMPUAN KOSAKATA PADA ANAK USIA 5-6 TAHUN DI KB ABU HURAIRAH MALIKIAN - Ulandari, Sri; Miranda, Dian; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to determine the effect of the picture story book method on the vocabulary skills of children aged 5"“6 years at KB Abu Hurairah Malikian. The research method used is an experiment with a form of quantitative research. The data sources for this research were the children's test sheets and the observation sheets of the PAUD KB teacher Abu Hurairah Malikian. The results of the study showed that the pre-observation (pre-test) vocabulary skills in children obtained an average value of 8.45 with the ability of vocabulary skills in children (65%). While the ability of vocabulary skills in children after being given the story method treatment (post-test) obtained an average value of 11.55 with the ability of vocabulary abilities in children (86%). Children's learning outcomes experienced a greater increase, meaning that there was an influence of the picture story book method on the vocabulary abilities of children aged 5"“6 years at PAUD KB Abu Hurairah Malikian.